Anticipating Cure: Blood and Urine Cultures Before Starting Antibiotics in Patients Admitted in Medical and Surgical Wards from Emergency Department at Lady Reading Hospital MTI, Peshawar - Daud, Muhammad; Abdullah, Muhammad; Zubair , Muhammad; Ahmad, Naveed; Uzair, Muhammad; Khan, Sheheryar; Waseem Ulllah; Shah, Pir Asad Ali (Indus Journal of Bioscience Research, 2025)
Background: This medical review examines whether Lady Reading Hospital Peshawar follows IDSA recommendations when obtaining blood and urine cultures before starting antibiotics for new patients coming from ED. The accuracy of blood and urine culture tests depends on proper specimen collection procedures yet healthcare teams only stick to these methods inconsistently which leads to inappropriate antibiotic use and raises patient risks. Methodology: Staff from Lady Reading Hospital reviewed 200 past patient records through HMIS to perform this analysis. Our sample consisted of blood cultures taken from 100 patients alongside 100 urine tests. The review examined to what extent healthcare facilities followed IDSA recommendations and aimed for 95% implementation accuracy. The research team gathered information about patients such as age, culture testing schedule, and antibiotic treatment details. The audit uncovered system challenges affecting patient care and doctors’ decision structures. Results and Discussion: The examination revealed poor culture practices with tests taken before antibiotics only in 10% of blood culture cases and 2% of urine culture cases which fell far below the desired 95% rate. The busy ED environment made clinicians rush the processing of patient samples which led to reduced adherence to antibiotic protocols and increased the risk of developing drug-resistant bacteria. Conclusion: The audit shows Lady Reading Hospital does not follow proper guidelines by taking diagnostic cultures before starting antibiotic treatment. Clinicians need education and workflow changes plus real-time monitoring to meet IDSA rules and help patients get better results.